Corporate Governance With Conscience - A Gateway for Economic Prosperity - Chandel, Kulbhushan; Kumar, Raj; Kant, Kamal (Prabandhan: Indian Journal of Management, 2009)
Governance based on rules, regulations, legal framework, codes of conduct and ethics will lead to creative manipulative practices by the people so responsible for this by finding the loopholes and ways and means to side step every such prescription. Greed leads to clouding of the soul, and hence a behavior that is totally self-serving-seeking money, power and prestige on ever non-satisfying journey at the cost of interests of others. The type of leadership and its character are the most important factors in governance with conscience. Wisdom lies in awakened self-interest which is always served when one serves others, and cares for the humanity at large. Self-seeking behavior can be perceived to be beneficial in the short-run, but in reality it is not. Long-run interests always depend on building blocks of short-run motives. One cannot be ethical in the long-run being unethical in the short-run. Short-run supplements the long-run. Governance by leaders of character based on conscience will lead to make corporations useful to the humanity.